The inverse associations between composite-dietary-antioxidant-index and sarcopenia risk in US adults - Wang, Kang; Zhou, Qin; Jiang, Zhongbiao; Liu, Shiping; Tang, Hanfen (Frontiers in Endocrinology, 2024)
Background: It remains unknown whether composite-dietary-antioxidant-index (CDAI) is associated with the risk of sarcopenia. This study investigated the association of CDAI with sarcopenia risk among general US adults. Methods: A total of 10,093 participants were enrolled in the National Health and Nutrition Examination Surveys (NHANES) from 6 survey cycles (2003-2004, 2005-2006, 2011-2012, 2013-2014, 2015-2016 and 2017-2018). Multivariate logistic regression was carried out to examine the relationship between CDAI and the risk of sarcopenia. Restricted cubic spline (RCS) curves were employed to analyze nonlinear relationships. Results: In a multi-variable logistic regression model adjusting for demographics, lifestyle, economic status and other dietary factors, higher CDAI score was related to a lower risk of sarcopenia among US adults. Compared the highest quartile of CDAI score with the lowest, the OR and 95%CI were 0.49 (0.31-0.75). Furthermore, the RCS demonstrated a linear dose-response relationship between CDAI and sarcopenia (Pnon-linearity=0.92). These results remained consistent across subgroups stratified by age, sex, physical activity, drinking status, body mass index (BMI), smoking habits, energy intake, and Healthy Eating Index (HEI) score. In addition, the favorable associations of CDAI were primarily attributed to Vitamin E intake. Conclusion: A higher CDAI score was associated with a lower risk of sarcopenia. According to these results, a greater adherence to CDAI may benefit sarcopenia prevention in adults.